2017
DOI: 10.1111/jcpe.12833
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with pain and analgesic consumption following non‐surgical periodontal therapy under local anaesthesia and carried out by dental students

Abstract: Aim: Evaluate factors associated with pain and analgesic consumption following nonsurgical periodontal therapy. Materials and methods:The sample consisted of 218 patients with chronic periodontitis, submitted to non-surgical scaling and root planing under local anaesthesia at a public dental service in southern Brazil. The data collection instruments included a demographic questionnaire, as well as State-Trait Anxiety Inventory, Corahʼs Dental Anxiety Scale, Visual Analogue Scale, Numerical Rating Scale and Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 71 publications
(108 reference statements)
3
26
0
Order By: Relevance
“…It has been suggested by Schirmer et al that post‐NSPT pain is associated with dental anxiety and baseline inflammation . In their study, the prevalence of pain after NSPT with local anesthetic was higher for patients with severe periodontal inflammation, defined as the presence of at least 4 sites with a probing depth of 6 mm or more.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…It has been suggested by Schirmer et al that post‐NSPT pain is associated with dental anxiety and baseline inflammation . In their study, the prevalence of pain after NSPT with local anesthetic was higher for patients with severe periodontal inflammation, defined as the presence of at least 4 sites with a probing depth of 6 mm or more.…”
Section: Discussionmentioning
confidence: 65%
“…24 It has been suggested by Schirmer et al that post-NSPT pain is associated with dental anxiety and baseline inflammation. 14 though the microbiota is almost suppressed by CHX, the microbiota spontaneously return to that observed after mechanical means alone. 26 This reinforces the notion that the microenvironment is critical in controlling the actual bacterial composition of the local microbiome, and that the microbiota will tend to return to that characteristic of the specific individual, once antimicrobial means are withdrawn.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As a major component of dental fear, fear of pain associated with dental treatment was identi ed [41]. SRP is often associated with pain and discomfort, albeit the occurrence of pain is variable and dramatically different among patients [20]. The VAS scores representing the pain perceived during periodontal procedures range from approximately 20-80mm [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…According to Santuchi et al, patients with mild to moderate chronic periodontitis based on the previous classi cation (1999) exhibited worse clinical periodontal status with higher dental fear level [13]. Schirme et al reported that severe periodontal in ammation (≥4 sites with≥6 mm PD) was related to pain and dental fear during SRP [20]. Levin et al noted that patients with aggressive periodontitis (AgP) in previous classi cation (1999) demonstrated higher dental fear levels [8].…”
Section: Introductionmentioning
confidence: 99%